A new Sarcoglottis (Orchidaceae: Spiranthinae) from the southern Brazilian Amazon - Engels, Mathias Erich; Smidt, Eric De Camargo (Phytotaxa, 2021)
Sarcoglottis matogrossensis, a new orchid species from the southern edge of the Brazilian Amazon, is described and illustrated. The novelty was found growing as humicolous and saxicolous in the understory of the seasonal evergreen forest on the banks of the Teles Pires River, in the north-central region of Mato Grosso state. Sarcoglottis matogrossensis is similar to S. amazonica, S. maroaënsis, S. metallica, and S. neillii, differing from these in the proportionally narrower and longer light green leaves that may or may not have white spots, the flowering that occurs after the senescence of the leaves, and the petals with apices conspicuously free, acute, and reflexed. We suggest the category of Data Deficient (DD) due to the scarcity of collections and the unknown effect of illegal deforestation on the populations of this species, pending further studies.